Sex For Revenge In Jackie Collins's The Love Killers Novel 1989): A Psychoanalytic Approach - Supriyadi, Aan Agus; , Drs. Abdillah Nugroho, M. Hum; , Drs. Sigit Haryanto, M.Hum (2014)
The problem of this study is the sex for revenge reflected in Jackie Collins's The Love Killers novel. The objective of this study is to analyze the novel based on the structural elements and to analyze the novel based on the psychoanalytic approach. The type of this research is qualitative research. Type of data of the study is text taken from two data sources: primary and secondary. The primary data source is The Love Killers novel written by Jackie Collins in 1989. Then the secondary data sources are other materials taken from books, author's biography, essay, comments, critics and internet related to the study. Both data are collected by conducting library research and analyzed by descriptive analysis. Based on the analysis, the researcher portrays some conclusions. First, based on the structural analysis of each elements, it shows that the character and characterization, setting, plot, point of view, style, and theme are supporting each other to produce a good quality and interesting novel. Second, based on the psychoanalytic analysis, the study shows that the problem faced by the major character is the own psychology condition to decide the appropriate ways for his life. This novel also shows the process that involves sex for revenge to get the complacency for her feel.